Classroom management and learning media effects on student achievement in resource-limited coastal primary schools: evidence from two Indonesian coastal regions - Rudolf Kempa; Paul Arjanto; Patrisius Rahabav; Emma Rumahlewang; Beatrix Tomasila; Vando Kristi Makaruku; Lifia Meiliza Wiyono; Dara Kakisina (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study examined the influence of classroom management and learning media availability on student achievement in coastal primary schools in Mamala and Morela. Using a quantitative design, data were collected from 49 classroom teachers through questionnaires, observation, and documentation, and analyzed using descriptive statistics and multiple linear regression. The findings showed that classroom management and student achievement were categorized as good, while learning media availability was fairly good but uneven across schools. Partially, classroom management had a positive and significant effect on student achievement (β = 0.488, p < .001), whereas learning media availability was not significant when tested independently (β = 0.245, p = .090). Simultaneously, both variables significantly influenced student achievement (F = 7.386, p = .002), with classroom management emerging as the stronger predictor. The results emphasize the importance of effective classroom management and the contextual use of learning media in improving learning outcomes in resource-constrained coastal schools. These findings provide practical implications for teacher training and equitable provision of low-cost instructional media.